Changes of temporomandibular joint space volume during 1 year after transoral vertical ramus osteotomy in patients with mandibular asymmetry - Sung Jun Bae; Hae-Seong Yong; Haneul Lee; Hye-Sun Kim; Jong-Ki Huh; Jae-Young Kim (Scientific Reports)
Abstract This retrospective study aimed to evaluate the difference in the temporomandibular joint (TMJ) space volume between the deviated (Dev) and non-deviated (NDev) side following transoral vertical ramus osteotomy (TOVRO) in patients with mandibular prognathism combined with asymmetry using reconstructed 3-dimensional images. Sixty joints from 30 patients who underwent TOVRO between January 2018 and December 2021 were included. Computed tomography (CT) or cone-beam CT was performed before surgery (T0), and 6 (T1) and 12 months postoperatively (T2). The volume of the overall joint space (Vjs) and its compartments (i.e., the anterior, posterior, medial, and lateral joint spaces) were calculated at each time point. A linear mixed model and repeated-measures covariance pattern with unstructured covariance were used. Vjs increased at T1 compared to T0 and decreased at T2 compared to T1 (p < 0.0001). Furthermore, the volume changes over time were statistically significant in all compartments (p < 0.05); however, there was no significant difference in the Vjs and its compartments between the Dev and NDev side over time (p > 0.05). Adjustments for sex and mandibular movements did not affect the results. This study can provide the basis in TMJ spatial change and predicting the prognosis after TOVRO in facial asymmetry.